Hyperinsulinemia rather than insulin resistance itself induces blood pressure elevation in high fat diet-fed rats. (2nd October 2020) - Wang, Hui; Tian, Yaqiang; Chen, Yanyan; Shen, Xiaoxia; Pan, Lin; Li, Guangwei
ABSTRACT: Objective: To investigate if insulin resistance per se or the accompanying hyperinsulinemia induced hypertension and its underlying mechanisms. Methods: Sprague-Dawley rats were randomized into normal diet-fed group (ND group) and high-fat diet-fed group (HFD group). Then, the HFD group was further randomly divided into the control group (HFD_C group), the PIO group (treated with pioglitazone), the STZ_DM group (to induce diabetes with streptozotocin) and the DM+Ins group (streptozotocin injection followed by insulin treatment). Insulin sensitivity, plasma insulin, endothelin-1, norepinephrine, aldosterone, angiotensinⅡ and 24-h urinary sodium excretion (USE) levels of the groups were measured and analyzed. A multiple stepwise regression analysis method was applied to exam our hypothesis. Results: Compared to HFD_C group, the groups with lower plasma insulin, the PIO group and STZ_DM group, showed higher USE and lower blood pressure. The groups with higher plasma insulin (but same level of insulin resistance), the HFD_C group and DM+Ins group, showed lower USE and higher blood pressure. The 24-h urinary sodium excretion was the most important contributor to the significant changes of blood pressure with an R 2 of 25.2% in this animal experiment. Conclusions: It is the compensatory hyperinsulinemia rather than insulin resistance per se that causes blood pressure elevation. The urinary sodium excretion is the key mediator among the multiple mechanisms. Therapies targeting hyperinsulinemia and restricting salt intake may favor a better control of hypertension associated with insulin resistance.